2016
DOI: 10.1186/s12883-016-0540-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial to evaluate the efficacy and usability of a computerised phone-based lifestyle coaching system for primary and secondary prevention of stroke

Abstract: BackgroundOne of the most effective current approaches to preventing stroke events is the reduction of lifestyle risk factors, such as unhealthy diet, physical inactivity and smoking. In this study, we assessed the efficacy and usability of the phone-based Computer-aided Prevention System (CAPSYS) in supporting the reduction of lifestyle-related risk factors.MethodsA single-centre two-arm clinical trial was performed between January 2013 and February 2014, based on individual follow-up periods of six months wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 20 publications
(12 reference statements)
1
35
1
1
Order By: Relevance
“…The existence of the current inpatient rehabilitation and outpatient care should be sustainable. Many forms telerehabilitation as a form of post-stroke intervention may show promising results (van de Ven, Schmand, Groet, Veltman, & Murre, 2015). By using the telerehabilitation system, it is possible to provide rehabilitation services at the patient's home or in the form of community-based technology, allowing the healthcare professionals to monitor a patient's health status and to identify the conditions that require improvement before ill effects occur (J.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of the current inpatient rehabilitation and outpatient care should be sustainable. Many forms telerehabilitation as a form of post-stroke intervention may show promising results (van de Ven, Schmand, Groet, Veltman, & Murre, 2015). By using the telerehabilitation system, it is possible to provide rehabilitation services at the patient's home or in the form of community-based technology, allowing the healthcare professionals to monitor a patient's health status and to identify the conditions that require improvement before ill effects occur (J.…”
Section: Discussionmentioning
confidence: 99%
“…By using the telerehabilitation system, it is possible to provide rehabilitation services at the patient's home or in the form of community-based technology, allowing the healthcare professionals to monitor a patient's health status and to identify the conditions that require improvement before ill effects occur (J. Kim et al, 2016;van de Ven et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Additionally, Spassova et al found that participants (n ¼ 94) who received a phone-based, algorithmic-automated lifestyle information provided twice a week for 6 months had favorable outcomes for BP, cholesterol, triglycerides, and diet. 119 Maasland et al (n ¼ 57) compared stroke education provided by a physician in combination with computerized lifestyle education with usual care with a physician. 127 Both studies corroborated that education provided at predetermined intervals (i.e., at 10 weeks, 5 and 8 months) and over the computer were not more effective than usual care with a physician.…”
Section: Lifestyle Education or Information Provisionmentioning
confidence: 99%
“…7 Bu konuda yapılan araştırmalarda, inme geçiren hastaların yaşam kalitesinin yükseltilmesinde özellikle hemşirelik bakım, uygulama ve girişimlerinin son derece önemli rol oynadığı bildirilmektedir. 10,11 Hemşirelerin, hastaların bakım gereksinimlerini optimum düzeyde karşılayabilmesi, hemşirelik bakımının standartlar doğrultusunda planlanması, uygulanması ve değerlendirilmesine bağlıdır. Bakımda ortak bir dil oluşturulması, bireyin holistik ve hümanistik bir yaklaşım doğrultusunda ele alınması, uygulamaların kanıta dayandırılması, bakımın sistematik bir yaklaşımla sunulması ve verilen bakımın kalitesinin güvence altına alınması önemlidir.…”
unclassified